Preoperative dual antiplatelet therapy increases bleeding and transfusions but not mortality in acute aortic dissection type A repair. (16th January 2019) - Hansson, Emma C; Geirsson, Arnar; Hjortdal, Vibeke; Mennander, Ari; Olsson, Christian; Gunn, Jarmo; Zindovic, Igor; Ahlsson, Anders; Nozohoor, Shahab; Chemtob, Raphaelle A; Pivodic, Aldina; Gudbjartsson, Tomas; et al.
Abstract: OBJECTIVES: Acute aortic dissection type A is a life-threatening condition, warranting immediate surgery. Presentation with sudden chest pain confers a risk of misdiagnosis as acute coronary syndrome resulting in subsequent potent antiplatelet treatment. We investigated the impact of dual antiplatelet therapy (DAPT) on bleeding and mortality using the Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD) database. METHODS: The NORCAAD database is a retrospective multicentre database where 119 of 1141 patients (10.4%) had DAPT with ASA + clopidogrel ( n = 108) or ASA + ticagrelor ( n = 11) before surgery. The incidence of major bleeding and 30-day mortality was compared between DAPT and non-DAPT patients with logistic regression models before and after propensity score matching. RESULTS: Before matching, 51.3% of DAPT patients had major bleeding when compared to 37.7% of non-DAPT patients ( P = 0.0049). DAPT patients received more transfusions of red blood cells [median 8 U (Q1–Q3 4–15) vs 5.5 U (2–11), P < 0.0001] and platelets [4 U (2–8) vs 2 U (1–4), P = 0.0001]. Crude 30-day mortality was 19.3% vs 17.0% ( P = 0.60). After matching, major bleeding remained significantly more common in DAPT patients, 51.3% vs 39.3% [odds ratio (OR) 1.63, 95% confidence interval (CI) 1.05–2.51; P = 0.028], but mortality did not significantly differ (OR 0.88, 95% CI 0.51–1.50; P = 0.63). Major bleeding was associated with increased 30-day mortality (adjusted OR 2.44, 95% CI 1.72–3.46; P < 0.0001). CONCLUSIONS: DAPT prior to acute aortic dissection repair was associated with increased bleeding and transfusions but not with mortality. Major bleeding per se was associated with a significantly increased mortality. Correct diagnosis is important to avoid DAPT and thereby reduce bleeding risk, but ongoing DAPT should not delay surgery.